Personal Similarities between Ghalib and Iqbal - Ashufta, Ashfaq Ahmad; Waheed, Sameeqa; Gul, Rubina (sourcecoder, 2022)
Ghalib and Iqbal are two universal poets of Urdu due to their intellectual and revolutionary style. Whose uniqueness is stamped? There is a long series of research, criticism and praise related to the personality and art of both. Both are poets of thoughts and values. Both gave four moons to Urdu poetry. Iqbal paid tribute to Ghalib in his poem Mirza Ghalib (published in 1091 AD). In this poem, the way Ghalib's intellectual and artistic perfection was felt on a universal level is a definite proof of Iqbal's mental closeness and devotion to Ghalib.